PENGGUNAAN MEDIA DARING (DALAM JARINGAN) PADA MATA PELAJARAN AQIDAH AKHLAQ DALAM MENUMBUHKAN MINAT BELAJAR PESERTA DIDIK KELAS XI AGAMA I MADRASAH ALIYAH NEGERI II KABUPATEN MALANG - Khovadli Ocvando; Chalimatus Sa’dijah; Kukuh Santosa (VICRATINA, 2020)
End of 2019 until now the world has been shaken by the Covid-19 virus pandemic, the pandemic has changed the life systems of several sectors, one of which is the education sector, with this pandemic humans are required to limit social interaction with other humans, limiting these interactions requires school institutions to diverting learning activities from home to school by using online media in learning, in this case online media are expected to continue to foster student learning interest, especially in the subject of Aqidah Akhlaq, this study discusses several subjects including: how to readiness of teachers in online learning, how the stages are, and how the supporting and inhibiting factors in fostering students' learning interest, this study uses a type of qualitative research, with a phenomenological approach and documentation method. In this study found descriptive results in the form of a teacher preparing for the use of online media based on the ability of students, the teacher gives assignments through the following stages of delivery of material, 1. The teacher opens the lesson by greeting, 2. The teacher rewards the students who are enthusiastic, 3. The teacher gives material, 4. Students begin working on Assignments and discussing, 5. Students collect Assignments. In this study the results of supporting factors and obstacles to the use of online media include, among others, 1. Readiness of facilities, 2. Students' desires for Aqeedah subjects, 3. Number of assignments given, 4. Environment of students